The National Identity of The Kingdom of Saudi Arabia In History and Government - Riskawati, Riskawati; Herisman , Muh. (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
This research aims to comprehensively understand the historical journey, government system, national Identity, and civic values that shape the character of the Saudi Arabian nation. By using in-depth literature review methods from various international books and journals, it shows that Saudi Arabia has an important role in the history and civilization of Islamic world. Saudi Arabia is known as the birthplace of the Prophet Muhammad (peace and blessings of Allah be upon him) and the founding of the two holy cities of Islam, namely Mecca and Medina. Founded in 1932 by King Abdulaziz bin Saud, Saudi Arabia is an absolute monarchy based on Islamic law and adheres to the Hanbali school of thought. The relationship between religion and state in Saudi Arabia is very close, especially with the influence of the teachings of Muhammad ibn Abd al-Wahhab which is the basis of the Kingdom's religious legitimacy. Islamic religious values as a national identity greatly influence the character of Saudi Arabian society, including in the economic and educational sectors. Islamic law as the state constitution makes the Al-Quran and Sunnah of the Prophet Muhammad sallallaahu alaihi wasallam as a source of reference in running the State. By maintaining religious foundations as the basis of national ideology, Saudi Arabia not only strengthens its position as the spiritual center of the Islamic world, but also as an important actor in contemporary global society.